The NBA and youth basketball: Recommendations for promoting a healthy and positive experience - DiFiori, J. P.; Güllich, A.; Brenner, J. S.; Côté, J.; Hainline, B.; RyanIII, E.; Malina, R. M. (Sports Medicine, 2018)
Participation in sports offers both short-term and long-term physical and psychosocial benefits for children and adolescents. However, an overemphasis on competitive success in youth sports may limit the benefits of participation, and could increase the risk of injury, burnout, and disengagement from physical activity. The National Basketball Association and USA Basketball recently assembled a group of leading experts to share their applied research and practices to address these issues. This review includes the group`s analysis of the existing body of research regarding youth sports participation and the related health, performance, and psychosocial outcomes. Based upon this, age-specific recommendations for basketball participation are provided that aim to promote a healthy and positive experience for youth basketball players.